2015
DOI: 10.1007/s00408-015-9778-7
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate pH in Lung Cancer, the Impact of Clinical Factors

Abstract: Although, EBC pH is unchanged in lung cancer, lower EBC pH values are associated with distinct phenotypes. Our findings could facilitate further research on airway acidity in lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The results of this study indicated that this particular neoplastic process also did not affect pH. Furthermore, no statistical differences in EBC pH were observed between patients with different stages of tumor growth [56,57]. However, two publications have provided conflicting reports on the impact of tumor histology.…”
Section: Lung Cancermentioning
confidence: 48%
See 3 more Smart Citations
“…The results of this study indicated that this particular neoplastic process also did not affect pH. Furthermore, no statistical differences in EBC pH were observed between patients with different stages of tumor growth [56,57]. However, two publications have provided conflicting reports on the impact of tumor histology.…”
Section: Lung Cancermentioning
confidence: 48%
“…Nevertheless, EBC pH levels are not a predictive factor for survival in lung cancer populations. It should also be noted that other diseases, such as chronic heart failure, diabetes, and chronic renal failure, do not influence EBC pH [57].…”
Section: Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, no statistical differences in EBC pH were observed between patients with different stages of tumor growth [56,57]. However, two publications have provided conflicting reports on the impact of tumor histology.…”
Section: Lung Cancermentioning
confidence: 97%